PROSES KREATIF DAN MANIFESTASI ESTETIKA MUSIKAL PADA IRINGAN TARI KIRANA RASMI - I Made Dwi Andika Putra; I Ketut Garwa; Ni Putu Hartini; I Nyoman Kariasa; Putu Tiodore Adi Bawa (Universitas Hamzanwadi, 2026)
This research aims to describe the creative process of creating the accompaniment of the Official Kirana Dance and analyze the musical aesthetic manifestations formed in the work. Kirana Rasmi conceptually raises the idea of